2019
DOI: 10.1002/ejlt.201900114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Virgin Almond and Hazelnut Oils and Their By‐Products

Abstract: Various cultivars of almonds (“Ferragnes,” “Guara,” “Largueta,” and “Marcona”) and hazelnuts (“Negret,” “Pauetet,” and “Tonda”), particularly their virgin oils and by‐products, are evaluated in this study. The almond and hazelnut virgin oils present high contents of oleic acid (59–73% and 76–80%, respectively) and α‐tocopherol (420–542 and 310–378 mg kg–1, respectively), as compared with other virgin vegetable oils. Aldehydes are the major contributors to their aromatic profile (54–74% almond oil and 30–40% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The richness of tocopherols in almond oil contributes to the antioxidant properties of oils; they also have protective roles in biological systems as well as other neuroprotective properties [19]. Our results are similar to those recorded in Spain 475 mg/kg [20] and higher compared to the ones obtained in Turkey (186.6 mg/kg) [21]…”
Section: Total Phenols and Tocopherol Content Of Almond Oilssupporting
confidence: 87%
“…The richness of tocopherols in almond oil contributes to the antioxidant properties of oils; they also have protective roles in biological systems as well as other neuroprotective properties [19]. Our results are similar to those recorded in Spain 475 mg/kg [20] and higher compared to the ones obtained in Turkey (186.6 mg/kg) [21]…”
Section: Total Phenols and Tocopherol Content Of Almond Oilssupporting
confidence: 87%
“…The interest aroused by these substances has boosted the development of new methods for their determination, increasing exponentially the published articles about them. Another important source of data is due to the recent interest in almond oil extraction as virgin edible oil [ 11 , 12 , 13 , 30 , 31 , 32 , 33 , 34 , 35 ]. In this sense, almond oil has been widely characterized, but oil extraction industries generate a by-product derived from the grinding of the pressing cake, which originates a partially defatted flour where the non-lipidic fraction takes on a special relevance.…”
Section: Chemical Composition Of Almond Kernelmentioning
confidence: 99%
“…Tree nuts contain very low amounts of carotenoids [ 27 ]. Marginal pigments content has been found in wild almond kernels [ 92 ], and the only study that indicates the chlorophyll and carotenoid content for cultivated almond kernels is due to Ojeda-Amador et al [ 35 ], who found 8.5–18 mg/kg of chlorophyll and 5.3–8.8 mg/kg of carotenoids in almond oils. Carotenoids concentration in almond kernels is low; consequently, it does not constitute an important dietary source of these substances [ 97 ].…”
Section: Phytochemical Compounds Of Almond Kernelmentioning
confidence: 99%
See 2 more Smart Citations